A breathtaking case of pulmonary hypertension with frightening complications and intertwining different etiologies - YILDIZELİ, BEDRETTİN (My University, 2023)
Pulmonary hypertension (PH) is a major health problem with increasing awareness. Although most common cause of PH is left heart disease (Group 2 PH), life-threatening complications occur mostly in Group 1 (pulmonary arterial hypertension) and Group 4 (chronic thromboembolic PH) patients. Although external compression of the left main coronary artery (LMCA) due to pulmonary artery dilatation is rare, it is a life-threatening complication since it causes myocardial ischemia and sudden cardiac death. In addition, PH is more than a single clinical entity due to its complex mechanism in which more than one subgroup may develop over time in the same patient. This complex mechanism challenges us when diagnosing the patient and faces us with life-threatening complications. In this case; we report a pulmonary arterial hypertension patient applied to our clinic with progressive dyspnea and recent angina, after detection of LMCA ostial stenosis, the patient was treated with intravascular ultrasound-guided stent implantation. In the further follow-ups, the patient underwent the pulmonary endarterectomy operation due to the diagnosis of chronic thromboembolic pulmonary hypertension secondary to newly diagnosed primary antiphospholipid syndrome.

Pulmoner hipertansiyon (PH) giderek farkındalığı artan önemli bir sağlık sorunudur. PH’nin en sık nedeni sol kalp hastalığı (Grup 2 PH) olmasına rağmen, yaşamı tehdit eden komplikasyonlar sıklıkla Grup 1 (pulmoner arteriyel hipertansiyon) ve Grup 4 (kronik tromboembolik pulmoner hipertansiyon) olan hastalarda görülmektedir. Ancak pulmoner arter dilatasyonuna bağlı gelişen sol ana koroner arterin (LMCA) eksternal basıya uğraması, nadir olmakla birlikte miyokardiyal iskemiye ve ani kardiyak ölüme yol açması nedeniyle hayatı tehdit eden bir komplikasyondur. Ayrıca PH tek bir klinik antiteden daha fazlası olup, aynı hastada zaman içinde birden fazla alt grubun gelişebileceği karmaşık bir mekanizmaya sahiptir. Bu karmaşık mekanizma, hastaya teşhis koyarken bizleri zorlarken ve hayatı tehdit eden komplikasyonlarla da karşı karşıya getirmektedir. Bu vakada; kliniğimize progresif nefes darlığı ve son zamanlarda artan anjina şikayeti ile başvuran, LMCA ostial stenozu saptandıktan sonra IVUS eşliğinde stent implantasyonu ile başarılı bir şekilde tedavi edilen bir pulmoner arteriyel hipertansiyon hastasını sunmaktayız. İlerleyen takiplerinde hastaya, yeni tanı primer antifosfolipid sendromuna sekonder gelişen kronik tromboembolik pulmoner hipertansiyon nedeniyle pulmoner endarterektomi operasyonu uygulanmıştır
Korkutucu komplikasyonları ve karmaşık etiyolojileri ile nefes kesen bir pulmoner hipertansiyon vakası
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Kronik tromboembolik pulmoner hipertansiyon; perkütan koroner girişimler; pulmoner endarterektomi; pulmoner hipertansiyon; Chronic thromboembolic pulmonary hypertension; p